Stepping Out of the Ivory Tower for Ocean Literacy - Kopke, Kathrin; Black, Jeffrey; Dozier, Amy (Frontiers in Marine Science, 2019)
The Ocean Literacy movement is predominantly driven forward by scientists and educators working in subject areas associated with ocean science. While some in the scientific community have heeded the responsibility to communicate with the general public to increase scientific literacy, reaching and engaging with diverse audiences remains a challenge. Many academic institutions, research centers, and individual scientists use Social Network Sites (SNS) like Twitter to not only promote conferences, journal publications, and scientific reports, but to disseminate resources and information that have the potential to increase the scientific literacy of diverse audiences. As more people turn to social media for news and information, SNSs like Twitter have a great potential to increase ocean literacy, so long as disseminators understand the best practices and limitations of SNS communication. This study analyzed the Twitter account of MaREI – Ireland’s Centre for Marine and Renewable Energy – coordinated by University College Cork Ireland, as a case study. We looked specifically at posts related to ocean literacy to determine what types of audiences are being engaged and what factors need to be considered to increase engagement with intended audiences. Two main findings are presented in this paper. First, we present overall user retweet frequency as a function of post characteristics, highlighting features significant in influencing users’ retweet behaviour. Second, we separate users into two types – INREACH and OUTREACH – and identify post characteristics that are statistically relevant in increasing the probability of engaging with an OUTREACH user. The results of this study provide novel insight into the ways in which science-based Twitter users can better use the platform as a vector for science communication and outreach.